The Impact of CEO Narcissism Behavior on Firm Performance through Earnings Management - Muhammad Rusydi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The purpose of this study is to see if Narcissistic CEO behavior patterns lead to earnings management. This study looks at the signs of Narcissistic CEO management practices and how they relate to company performance in 19 Manufacturing Companies listed on the IDX from 2017 to 2019. There are 57 people in the sample. The method of research used in this study was quantitative research with a causal approach. The SPSS test tool for Windows 24.0 is used to test hypotheses by using Path analysis. The findings, CEO narcissism, impact earnings management behavior, but it also impacts company performance through earnings management practices or actions. The CEO is the custodian of data and has the power to make decisions, including policies. The accounting will make every effort to portray good performance through a positive image and profit achievement as expected by investors as an indicator of performance measurement; as a result, CEOs with high self-confidence will use accounting policies to practice earnings management by adding profit figures as needed and the investors' wishes or lowering the profit rate as necessary to achieve the desired results